Anaerobic threshold - a relatively useless concept for coaching - Billat, L.
Billat, L. V. (1996). Use of blood lactate measurements for prediction of exercise performance and for control of training: Recommendations for long-distance running. Sports Medicine, 22, 157-175. This article contains a very concise summary of the concept of anaerobic threshold and how it is depicted in the literature. The implications of each individual statement are particularly important given the pre-occupation of many coaches with this concept. The major points of the article are discussed below. Further features are introduced in the "Implications" section.